Variability in fruit characteristics of nutmeg (Myristica fragrans Houtt.) under Kerala conditions - Kumari, E V Nybe, D Mathew, H C Vikram, N Mini Raj, K T Presanna (Journal of Spices and Aromatic Crops, 2016)
Forty one accessions of nutmeg collected from diverse locations of Kerala of age 15 years were evaluated at Kerala Agricultural University, Thrissur during 2012–14. Among these accessions, 38 were females and three were monoecious. The accessions were evaluated based on 17 fruit characters recorded from two trees per accession during two consecutive bearing seasons. The statistical parameters viz., mean, range, phenotypic coefficient of variation (PCV), genotypic coefficient of variation (GCV), heritability (H2), genetic gain (GG) and genotypic correlation coefficients were calculated. High PCV and GCV were observed for the characters such as fruit weight, mace weight, mace volume, dry nut weight, kernel weight, fruit volume and number of fruits per tree. Heritability was high for all the characters except shell thickness. High GCV coupled with high heritability in the characters indicated the scope for yield improvement through selection based on these characters. Genetic gain was the highest for number of fruits per tree (144.3%) followed by mace characters viz., fresh and dry weight as well as volume of nut. Fruit weight was also significantly and positively correlated with fruit breadth, fruit volume and thickness of pericarp. Based on the results, accessions such as Acc. 9, Acc. 8 and Acc. 22 were found promising with respect to the economic characters viz., mace weight, nut weight, kernel weight and number of fruits per tree. These accessions can be used in further crop improvement programmes on nutmeg.